(untitled) (The Research of Medical Science Review, 2025)
Objective: To assess the diagnostic accuracy of Bronchoalveolar Lavage (BAL) gene xpert (Xpert MTB/RIF assay) in smear-negative and sputum-scarce patients to detect mycobacterium tuberculosis using mycobacterial culture as the gold standard. Study Design: Cross-sectional validation study Place and Duration of Study: Department of Pulmonology, Pakistan Institute of Medical Sciences (PIMS), Islamabad, from July 2024 to December 2024. Methodology: A total of 215 patients with suspected pulmonary tuberculosis who were either smear-negative or sputum-scarce were included. Smear-negative cases were defined as those with three sputum specimens negative for Acid-Fast Bacilli (AFB) on microscopy using the Ziehl-Neelsen (ZN) staining technique[8]. Sputum-scarce cases were those unable to produce sputum or provide sputum samples of less than 1 mL[8]. The diagnostic performance of BAL GeneXpert, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy, was calculated against the BAL culture results. Results: Frequency of BAL culture was 195 out of 215(90.6%).BAL GeneXpert demonstrated a sensitivity of 93.33%, specificity of 85%, PPV of 98.38%, NPV of 56.67% and overall accuracy of 92.56%. Tuberculosis was identified in 185 out of 215 cases using BAL gene xpert. Conclusion: BAL GeneXpert exhibits superior diagnostic accuracy in detecting tuberculosis among smear-negative and sputum-scarce patients, making it a reliable diagnostic tool in such cases.